INVESTMENT MARKETING AS DETERMINANT OF COMPETITIVENESS OF ENTERPRISES AT THE MARKET OF INVESTMENTS - Марія Олексіївна Базь; Є. А. Домашева (Ekonomìčnij Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni "Kiïvsʹkij Polìtehnìčnij Institut", 2015)
In the article considered the question of the importance of investment marketing in the modern market activity, innovativeness such services, its effectiveness in ensuring consumer effect on economic processes. Purpose of the article is to heave the interest to this methodology of work at the market, that is a powerful weapon, if to use it with a mind. Specified aspects of investment marketing, its essence, strategies, milestones, strategic planning, and principles. Also taken into account the urgency of the development of the marketing concept, based on a new type of thinking; specificity of the investment market; the tactics of relations with investors; methods of analysis of risk factors investment activity. General economic tendencies are taken into account and the aims of the mentioned type of activity, appropriateness of the use and development in the conditions of global changes, efficiency and effectiveness, are determined on to the market of Ukraine, prospects which arise up during realization of investment projects. Proven the inalienability investment marketing as determinant of competitiveness of enterprises at the market of investments.